Kesesuaian Habitat Rusa Timor di PT. Taman Satwa Semarang - Nurhayati, Irma; Partaya, Partaya; Priyono, Bambang (Life Science, 2020)
Timor deer (Cervus timorensis) is one of the endemic animals in Indonesia, whose natural distribution is found in Java, Sulawesi, Maluku and Nusa Tenggara. Timor deer has decreased in population due to habitat loss, habitat degradation, and hunting which causes its status to be vulnerable. Timor deer are conserved ex-situ at the PT. Taman Satwa Semarang. This study aims to assess the suitability of the habitat and welfare level management of Timor deer at PT. Taman Satwa Semarang. This research uses the method of observation and interview methods. Data analysis was carried out descriptively using evaluative comparison method with indicators of habitat suitability and level of animal welfare according to deer breeding requirements, predecessor research and Regulation of the Director General of PHKA Number: P. 6 / IV-SET / 2011. Results of the research on the suitability of the timor deer habitat were seen from the habitat conditions, reproduction and the level of animal welfare. The low birth rate of Timor deer at PT. Taman Satwa Semarang is thought to be due to a lack of feed, sex ratio and absence of marriage management. Animal welfare level at PT. Semarang Animal Park can be categorized as adequate, because there are still animal welfare components that need to be improved by the manager, especially the components that are free from thirst and hunger and free from fear and depression. Rusa timor (Cervus timorensis) merupakan salah satu satwa endemik di Indonesia yang persebaran alaminya terdapat di Pulau Jawa, Sulawesi, Maluku dan Nusa Tenggara. Rusa timor mengalami penurunan populasi akibat hilangnya habitat, degradasi habitat, dan perburuan yang menyebabkan statusnya rentan (vulnerable). Rusa timor dikonservasi secara ex-situ di Lembaga Konservasi PT. Taman Satwa Semarang. Tujuan dari penelitian ini yaitu untuk mengkaji kesesuaian habitat dan manajemen tingkat kesejahteraan rusa timor di PT. Taman Satwa Semarang. Penelitian menggunakan metode observasi dan metode wawancara. Analisis data dilakukan secara deskriptif dengan metode perbandingan evaluatif dengan indikator kesesuaian habitat dan tingkat kesejahteraan satwa menurut syarat penangkaran rusa, penelitian pendahulu dan Peraturan Dirjen PHKA Nomor: P. 6/IV-SET/2011. Hasil penelitian kesesuaian habitat rusa timor dilihat dari kondisi habitat, reproduksi dan tingkat kesejahteraan satwa. Rendahnya angka kelahiran rusa timor di PT. Taman Satwa Semarang diduga akibat kurangnya jumlah pakan, sex-ratio dan tidak adanya manajemen perkawinan. Tingkat kesejahteraan satwa di PT. Taman Satwa Semarang dikategorikan cukup baik, dikarenakan masih terdapat komponen kesejahteraan satwa yang perlu diperbaiki pengelola khususnya komponen bebas dari rasa haus dan lapar serta bebas dari rasa takut dan tertekan